Pembentukan Kepribadian Mental Sehat Perspektif Psikologi Islam - Musripah, Musripah (Madaniyah, 2018)
This study aims to determine the factors mental mental / mental disorders and preventive solutions. The loss of the meaning of life in modern life continues to develop. Through Islamic psychology approach is expected to form a healthy mental, which is an inner condition that is always in a state of calm, safe, and serene. Attempts to find inner peace can be done, among others, through personal salvation to God). Islam as a religion of Grace has a concept to answer it. Man is not only a creature in the physical, material, mental, and spiritual appearance. In building a healthy mental personality through some intervesies with familiar social problems, personality and soul disorders, then form a healthy mental through Islamic psychological approach. Â Keywords: Social problem, personality and soul disorder, mental health.